Refractory chronic cluster headache: a consensus statement on clinical definition from the European Headache Federation - Mitsikostas, Dimos D (J Headache Pain, 2014)
Chronic cluster headache (CCH) often resists to prophylactic pharmaceutical treatments resulting in patients’ life damage. In this rare but pragmatic situation escalation to invasive management is needed but framing criteria are lacking. We aimed to reach a consensus for refractory CCH definition for clinical and research use. The preparation of the final consensus followed three stages. Internal between authors, a larger between all European Headache Federation members and finally an international one among all investigators that have published clinical studies on cluster headache the last five years. Eighty-five investigators reached by email. Proposed criteria were in the format of the International Classification of Headache Disorders III-beta (description, criteria, notes, comments and references). Following this evaluation eight drafts were prepared before the final. Twenty-four (28.2%) international investigators commented during two rounds. Refractory CCH is described in the present consensus as a situation that fulfills the criteria of ICHD-3 beta for CCH with at least three severe attacks per week despite at least three consecutive trials of adequate preventive treatments. The condition is rare, but difficult to manage and invasive treatments may be needed. The consensus addresses five specific clinical and paraclinical diagnostic criteria followed by three notes and specific comments. Although refractory CCH may be not a separate identity these specific diagnostic criteria should help clinicians and investigators to improve patient’s quality of life.